Possible role of Tremella fuciformis polysaccharide in modulating in vitro digestion of potato starch digesta - Xilu Zhang; Yongxia Fu; Han Wang; Qun Shen; Zhenyu Liu; Yuanlong Chi (Food Chemistry: X, 2025)
The effect of deproteinized Tremella olysaccharide (DTP) on the in vitro digestion of potato starch (PS) was investigated. DTP reduced the hydrolysis rate of PS in a concentration-dependent manner, with digestion rates of 76.99 %, 72.03 %, and 29.73 % after 180 min for 0.3, 0.6, and 1.2 mg/mL DTP, respectively. DTP delayed digestion by shifting the kinetics from single-phase to biphasic behavior. It significantly inhibited pancreatic α-amylase (IC50 = 5.76 mg/mL) by modifying the enzyme's secondary structure and reducing substrate binding. Additionally, DTP enhanced digesta viscosity, which may have contributed to the reduction in postprandial glucose release, thereby supporting its role as a potential hypoglycemic agent. However, DTP exhibited minimal glucose adsorption, binding only 1.2 % of 100 mM glucose at 1.2 mg/mL. These findings suggest that DTP reduces starch digestion primarily by inhibiting α-amylase activity and increasing digestive viscosity, providing insights into its hypoglycemic potential.